Empowering patient’s relatives: How to do it right using the media - Khalib AL; Natrah MS (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Introduction : Relatives play an important role in patient care - not only providing social support but also help to complement the existing care. They must be empowered with relevant knowledge and skills of patient care including motivating patient towards immediate healing and acceptance of his fate. Although these are various approaches, the media is regarded as the most effective method in educating the family or the relatives. This paper highlights the significant role of the media as an educational tool to mobilize patient’s relatives in total patient care. Methodology : This is a review conducted on reports, observations and feedbacks gathered from various sources involved in patient education in hospital setting. It was endorsed by a series of in-depth expert forum under patient education module. Results : Relative empowerment has been identified to be as an important role and yet it is not fully utilized. The manpower resources are so scarce and crucial in patient as well as relative education. The media is the only alternative educational tool that could compliment the educational needs. Of all potential media available in the market we have recognized at least four types of media that can be optimally resourced and used. Through manipulation of its content and making it interactive, the role of media seemed to be extremely effective in patient management that include relatives. Conclusion : The role of media in relative’s education in support of patient care is undeniable. The media with the most potential should be identified and the management of its content to be enhanced. It must be incorporated with an interactive approach in order to have more self-involvement and undersatanding of its content.